PENERAPAN DISCOVERY LEARNING DALAM MENINGKATKAN PEMAHAMAN MEMBACA SISWA di SMK Neg.1 LHOKSEUMAWE - Rahmati Rahmati (Majelis Pendidikan Aceh, 2022)
This study aimed to improve the students ability in reading comprehension of grade 1 students in SMK Neg. 1 Lhokseumawe for the 2020/2021 academic year. The population and sample of this study were students of class 1 SMK Negeri 1 Lhokseumawe. There were two classes as the sample, accounting majors as the experimental group and computer network engineering majors as the control group. The data obtained is by collecting pre-test and post-test. The data were analyzed by calculating the t-test to find out the significant difference to the mean values of the two groups. Based on statistical analysis, it was found that the t-test for the experimental and control classes was -11.385 with a significance of 0.00. while the determined significance level is 0.005. This means that 0.00 < 0.05, this indicates that there is a significant difference for the posttest between the experimental and control classes. The difference in the posttest mean scores between the experimental and control classes was considered significant. To follow up on the results of this study, suggestions are needed to teach reading as an active and meaningful activity. Therefore, English teachers are expected to apply various strategies in the reading learning process.